Joining phenomena of stainless steel/aluminium alloy joint welded by thermal compensation resistance spot welding. (1st January 2014) - Qiu, Ranfeng; Shi, Hongxin; Yu, Hua; Zhang, Keke
Aluminium alloy and austenitic stainless steel were welded using a thermal compensation resistance spot welding technology. The interface region was observed using electron microscopy, and the temperature distribution on the welding zone was investigated as well. The results reveal that higher heat can be obtained in thermal compensation resistance spot welding in comparison with conventional one, and that the morphology and thickness of the reaction layer vary with the position at the welding interface.